Acceptance of Coffee Ground Compost Fertilizer Produced by Students of the Agricultural Engineering Study Program at Serambi Mekkah University for Farmers in Aceh Besar Regency - Chairuni AR; Nurul Akmal; Geta Ambartiasari (Postgraduate, University of Mataram, 2025)
This study aims to analyze the acceptance of coffee-ground compost fertilizer developed by students of the Agricultural Industrial Engineering Program, Universitas Serambi Mekkah, among farmers in Aceh Besar Regency. The analysis was conducted using two theoretical frameworks: the Technology Acceptance Model (TAM) and the Diffusion of Innovation (DOI). Data were collected through questionnaires from farmers, focusing on indicators such as fertilizer quality, ease of application, affordability, accessibility, and soil impact. The TAM analysis revealed that farmers hold a positive perception of the fertilizer’s usefulness and ease of use, influencing their attitudes and behavioral intentions toward adoption. Meanwhile, the DOI analysis highlighted the role of innovation characteristics, communication channels, time, and social systems in the diffusion process. This research provides an initial overview of the potential adoption of coffee-ground-based organic fertilizer as an environmentally friendly alternative to support sustainable agriculture in Aceh Besar.